A Question of Identity and Equality in Sports: Men's Participation in Men's Rhythmic Gymnastics. - Irene Kamberidou; Tsopani, Despina; Dallas, George; Patsantaras, Nikolaos (Nebula, 2009)
Spain has become the first country in the world to officially recognize and promote Men’s Rhythmic Gymnastics. In light of the Spanish Gymnastics Federation’s recent initiative (Feb. 2009) this paper examines corporeality and sport identity in ways that reflect processes of change, in exploring the interrelation of social theories, international dialogue and anachronistic gender-based ideologies that established gender stereotypes in competitive sports. Subsequently, this paper presents a case study and discusses the official recognition of men’s rhythmic gymnastics (RG) by the Federation of International Gymnastics (FIG). Despite gender stereotypes that depict this Olympic sport as unacceptable for the image of masculinity, the male body aesthetic, including masculine gender role identity, the rising involvement of boys and men in this sport throughout the globe can no longer be ignored. Incontestably rhythmic gymnastics for men and boys is growing and how far it will go remains to be seen. The socially constructed and historically specific nature of physicality, corporeality and sport identity need to be renegotiated since exclusions based on genetic characteristics are a contradiction to the value system of sport. (Olympic Charter, rule2 par. 5, 7/7/2007) Keywords: gender-inclusive, gender fluidity, gender identity, corporeality, genetic personification, men’s rhythmic gymnastics..